2019
DOI: 10.3390/ijerph16101779
|View full text |Cite
|
Sign up to set email alerts
|

Single Core Genome Sequencing for Detection of both Borrelia burgdorferi Sensu Lato and Relapsing Fever Borrelia Species

Abstract: Lyme disease, initially described as Lyme arthritis, was reported before nucleic-acid based detection technologies were available. The most widely used diagnostic tests for Lyme disease are based on the serologic detection of antibodies produced against antigens derived from a single strain of Borrelia burgdorferi. The poor diagnostic accuracy of serological tests early in the infection process has been noted most recently in the 2018 Report to Congress issued by the U.S. Department of Health and Human Service… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 69 publications
0
6
0
Order By: Relevance
“…The cfDNA sequencing method’s sensitivity was further improved by combining the results of the modified two-tiered serology testing to identify 86% of acute Lyme borreliosis cases. Additionally, a recent NGS detection study identified core genes within the Borreliella pangenome to increase the sensitivity of DNA-based Borreliaceae diagnostics [ 208 ]. Taken together, genomic Borreliella detection methods have significantly improved over the last decade.…”
Section: Borreliaceae Diagnosticsmentioning
confidence: 99%
See 3 more Smart Citations
“…The cfDNA sequencing method’s sensitivity was further improved by combining the results of the modified two-tiered serology testing to identify 86% of acute Lyme borreliosis cases. Additionally, a recent NGS detection study identified core genes within the Borreliella pangenome to increase the sensitivity of DNA-based Borreliaceae diagnostics [ 208 ]. Taken together, genomic Borreliella detection methods have significantly improved over the last decade.…”
Section: Borreliaceae Diagnosticsmentioning
confidence: 99%
“…Concurrently with the growth of Borreliellal/Borrelial genomics, a tentative preliminary pangenome, rather defined as the complete collection of all genes available within a species (or higher taxonomic unit), from existing sequenced and annotated Borrelia genomes was created. This research focused on B. burgforferi sensu stricto and the B. burgdorferi sensu lato complexes [ 208 , 274 ]. In this first pangenome study, several Lb spirochetes were chosen based on their host of origin, geo-locale origin, vector, and if they had been isolated from symptomatic individuals.…”
Section: Pangenomic Applicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…The PCR reaction for Babesia species was carried out using a pair of primers, GF2 and GR2, which made it possible to amplify the DNA section with a 559 bp base-pair-long fragment of the 18S rRNA conservative gene . PCR for Borrelia was performed according to the method described by Lee et al (2019) with the primers M1 and M2 used to amplify the 16S rRNA gene fragment of B. burgdorferi s.l., with a length of 357 bp.…”
Section: Polymerase Chain Reactionmentioning
confidence: 99%